The adoption, diffusion and impact of an auditing documentation software in a Singapore public accounting firm : a case study - Goh, Lay Hoon (2015)
The documentation of auditing work papers has generally been a manual process, where the auditor writes on the audit file using pen and paper. However, the use of IT in auditing generally and in documentation specifically has been increasing. The project team examined the decision process to adopt A+-, an audit documentation software in Deloitte and Touche (D&T) Singapore, identifying the various stages in this decision process. The project team discovered that all the five stages in Rogers' adoption framework were identified in the organisation's process to adopt A+. The project team studied the ways in which A+ was diffused in the organisation as well as the process of diffusion in the organisation. The project team found that training was the main strategy used to diffuse A+ to the users in the organisation. The diffusion process as discussed by McFarlan and McKenney was compared to the organisation's diffusion process and the project team concluded that the actual diffusion process was not fully implemented at the time of the research. This is because the later stages of McFarlan and McKenney's diffusion process model could not be seen in D&T's diffusion process . Finally, the project team looked at the effects of the use of A+ on the auditor, especially the impact on productivity and work satisfaction. The project team found that A+ had a mixed effect on auditor performance and work satisfaction. The report concludes with several recommendations on factors which should be considered in implementing new IT especially documentation technology in public accounting firms in Singapore.